Correlations of Weather and Time Variables with Visits of Trauma Patients at a Regional Trauma Center in Korea - Hyuk Jin Choi; Jae Hoon Jang; Il Jae Wang; Mahnjeong Ha; Seunghan Yu; Jung Hwan Lee; Byung Chul Kim (Journal of Trauma and Injury)
Purpose Trauma incidence and hospitalizations of trauma patients are generally believed to be affected by season and weather. The objective of this study was to explore possible associations of the hospitalization rate of trauma patients with weather and time variables at a single regional trauma center in South Korea. Methods Trauma hospitalization data were obtained from a regional trauma center in South Korea from January 1, 2017 to December 31, 2019. In total, from 6,788 patients with trauma, data of 3,667 patients were analyzed, excluding those from outside the city where the trauma center was located. Hourly weather service data were obtained from the Korea Meteorological Administration. Results The hospitalization rate showed positive correlations with temperature (r=0.635) and wind speed (r=0.501), but a negative correlation with humidity (r=−0.620). It showed no significant correlation (r=0.036) with precipitation. The hospitalization rate also showed significant correlations with time of day (p=0.033) and month (p=0.22). Conclusions Weather and time affected the number of hospitalizations at a trauma center. The findings of this study could be used to determine care delivery, staffing, and resource allocation plans at trauma centers and emergency departments.